Retinol-binding protein 4 expression in visceral and subcutaneous fat in human obesity - Bajzová, M; Kováčiková, M; Vítková, M; Klimčáková, E; Polák, J; Kováčová, Z; Viguerie, N; Vedral, T; Mikulášek, L; Šrámková, P; Srp, A; Hejnová, J; et al. (Physiological research, 2008)
Retinol binding protein 4 (RBP4) is a novel adipokine which might be involved in the development of insulin resistance. The aim of the study was to investigate the expression of RBP4 mRNA in subcutaneous and visceral fat depots and the relationship between RBP4 plasma and mRNA levels relative to indices of adiposity and insulin resistance. In 59 Caucasian women (BMI 20 to 49 kg/m(2)) paired samples of subcutaneous and visceral fat were obtained for RBP4, leptin and GLUT 4 mRNA analysis using reverse transcription-quantitative PCR. Euglycemic hyperinsulinemic clamp and computed tomography scans were performed. RBP4 mRNA levels as well as GLUT 4 mRNA and leptin mRNA levels were lower (P<0.001, P<0.01 and P<0.001, respectively) in visceral compared to subcutaneous fat. No differences were found in RBP4 mRNA expression in the two fat depots or in RBP4 plasma levels between subgroups of non-obese subjects (n=26), obese subjects without metabolic syndrome (n=17) and with metabolic syndrome (n=16). No correlations between RBP4 mRNA or plasma levels relative to adiposity, glucose disposal rate and GLUT 4 mRNA expression in adipose tissue were found. There was a weak positive correlation between plasma RBP4 and plasma triglycerides (r = 0.30, p<0.05) and between plasma RBP4 and blood glucose (r = 0.26, p<0.05). Regardless of the state of adiposity or insulin resistance, RBP4 expression in humans was lower in visceral than in subcutaneous fat. We found no direct relationship between either RBP4 mRNA or its plasma levels and the adiposity or insulin resistance.
Keywords: Insulin; Young Adult; nitrobřišní tuk; leptin; Insulin Resistance; RNA, Messenger; Male; adipozita; inzulinová rezistence; plazmatické proteiny vázající retinol; inzulin; počítačová rentgenová tomografie; Obesity; mladý dospělý; krevní glukóza; obezita; Adult; Aged; dospělí; mužské pohlaví; senioři; metabolický syndrom; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; Intra-Abdominal Fat; podkožní tuk; Retinol-Binding Proteins, Plasma; Metabolic Syndrome; Tomography, X-Ray Computed; lidé; ženské pohlaví; přenašeč glukosy typ 4; Humans; Subcutaneous Fat; Adiposity; Reverse Transcriptase Polymerase Chain Reaction; Female; Blood Glucose; lidé středního věku; Leptin; Glucose Transporter Type 4; Middle Aged